Load characteristics and inhalation risk assessment of benzene series (BTEX) pollutant in indoor air of Ghalyan and/ or cigarette cafes compared to smoking-free cafes. Issue 1 (1st January 2020) - Heydari, Gholamreza; Ranjbar Vakilabadi, Dariush; Kermani, Majid; Rayani, Mohammad; Poureshgh, Yousef; Behroozi, Mojtaba; Fanaei, Farzad; Arfaeinia, Hossein
ABSTRACT: To determine the concentration of benzene series (BTEX) compounds, 33 samples were collected from indoor air of Ghalyan cafés (GHC), cigarette cafés (CC) and smoking-free cafés (SFC) in Bushehr city, Iran, and analyzed using gas-chromatography - flame ionization detector (GC-FID). The results of this study indicated that the mean±SD values of ΣBTEX in GHC, CC and SFC cafés were 19.46 ± 6.07, 11.34 ± 5.21 and 2.26 ± 0.76 mg/m 3, respectively. The mean concentration of BTEX in the cafés with fruit-flavored tobacco was significantly higher than those in traditional cafés (p < 0.05). According to path analysis, the number of active waterpipe heads had the maximum impact on the production of pollutants inside the cafés. The results also indicated that the risk of exposure to BTEX in smoking cafés in Bushehr was very high; it can develop serious carcinogenic and noncarcinogenic risks.